Brain development, experience, and behavior. Issue 10 (24th December 2013) - Kolb, Bryan; Mychasiuk, Richelle; Gibb, Robbin
<x xml:space="preserve">Abstract</x> Brain development progresses through a series of stages beginning with neurogenesis and progressing to neural migration, maturation, synaptogenesis, pruning, and myelin formation. This review examines the literature on how early experiences alter brain development, including environmental events such as sensory stimuli, early stress, psychoactive drugs, parent‐child relationships, peer relationships, intestinal flora, diet, and radiation. This sensitivity of the brain to early experiences has important implications for understanding neurodevelopmental disorders as well as the effect of medical interventions in children. Pediatr Blood Cancer 2014; 61:1720–1723. © 2013 Wiley Periodicals, Inc.